Laminate and paper processed article using same

By forming a laminated structure of a thermoplastic resin layer, a paper substrate layer, a barrier layer and a sealing layer on the paper substrate, a barrier layer of polyurethane resin, a swellable layered silicate and a cationic resin, the shortcomings of the existing paper substrate in terms of gas and water vapor barrier properties are solved, and efficient recycling is achieved, reducing environmental pollution.

CN119789955APending Publication Date: 2025-04-08OJI HLDG CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380056320.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-01
Filing Date
2023-07-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing paper substrate layered material has insufficient gas and water vapor barrier properties, and it is difficult to recycle it after use, and there are environmental problems.

Method used

A laminate consisting of a thermoplastic resin layer, a paper base layer, a barrier layer and a sealing layer are used, and the barrier layer contains a polyurethane resin, a swellable layered silicate and a cationic resin. This configuration is used to improve gas and water vapor barrier properties.

Benefits of technology

It achieves a high degree of balance between gas and water vapor barrier properties, improves paper ratio (biomass ratio), and is easier to recycle after use, reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005257050950000291
    Figure BDA0005257050950000291
  • Figure BDA0005257050950000321
    Figure BDA0005257050950000321
  • Figure BDA0005257050950000331
    Figure BDA0005257050950000331
Patent Text Reader

Abstract

A laminate provided with a thermoplastic resin layer, a paper substrate layer, a barrier layer, and a sealant layer in this order, the barrier layer containing a urethane resin, a swellable layered silicate, and a cationic resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a laminate having barrier properties and also to a paper product using the laminate. Background Art

[0002] Packaging materials in which gas barrier properties such as oxygen barrier properties and water vapor barrier properties are imparted to paper substrates have been conventionally used in packaging of foods, medical products, electronic components, and the like to prevent deterioration of the quality of the contents.

[0003] As a method for imparting water vapor barrier properties and gas barrier properties to a paper substrate, a method of laminating a synthetic resin film or the like having excellent gas barrier properties on the paper substrate is generally used. However, the material obtained by laminating a synthetic resin film or the like on a paper substrate is difficult to recycle the paper, synthetic resin, etc. after use, and there are problems in terms of the environment.

[0004] Therefore, the development of gas barrier materials based on paper without using synthetic resin films etc. For example, Patent Document 1 (Japanese Patent Publication No. 2021-138434) describes the following technology: in a paper barrier material having a gas barrier layer and a heat seal layer sequentially provided on a paper substrate, the hydroxyl group and acid group of the resin used for the gas barrier layer are controlled. Summary of the invention

[0005] The paper barrier material described in Patent Document 1 has a single-layer barrier layer, which can reduce the amount of plastic material, but is not sufficient from the viewpoint of achieving a higher gas barrier property and a balance between gas barrier property and water vapor barrier property.

[0006] An object of the present disclosure is to provide a laminate having both high gas barrier properties and water vapor barrier properties and further improving the paper ratio (biomass ratio).

[0007] The present disclosure relates to the following <1> to <10>.

[0008] <1> A laminate comprising a thermoplastic resin layer, a paper base layer, a barrier layer, and a sealant layer in this order, wherein the barrier layer contains a polyurethane resin, a swelling layered silicate, and a cationic resin.

[0009] <2> The laminate according to <1>, wherein the polyurethane resin includes at least one selected from the group consisting of polyurethanes having a structural unit derived from meta-xylylene diisocyanate and hydroxy polyurethanes.

[0010] <3> The laminate according to <1> or <2>, wherein the barrier layer contains 1.0 to 20.0% by mass of the cationic resin.

[0011] <4> The laminate according to any one of <1> to <3>, wherein the barrier layer contains 30.0 to 80.0% by mass of the polyurethane resin.

[0012] <5> The laminate according to any one of <1> to <4>, wherein the barrier layer contains 5.0 to 30.0% by mass of the swelling layered silicate.

[0013] <6> The laminate according to any one of <1> to <5>, wherein the barrier layer further comprises at least one selected from the group consisting of a water-suspended polymer other than a polyurethane resin and a water-soluble polymer other than a polyurethane resin, the water-suspended polymer comprises an olefin-unsaturated carboxylic acid copolymer, and the water-soluble polymer comprises at least one selected from the group consisting of a vinyl alcohol polymer and a polyalkylene imine.

[0014] <7> The laminate according to any one of <1> to <6>, wherein the barrier layer further comprises a water-suspended polymer other than the polyurethane resin and a water-soluble polymer other than the polyurethane resin, and the barrier layer comprises the water-suspended polymer and the water-soluble polymer in at least the following combination of (A) or (B).

[0015] (A) Water-suspended polymer: ethylene-acrylic acid copolymer; water-soluble polymer: polyvinyl alcohol.

[0016] (B) Water-suspended polymer: ethylene-acrylic acid copolymer; water-soluble polymer: polyvinyl alcohol and polyethyleneimine.

[0017] <8> The laminate according to <6> or <7>, wherein the barrier layer contains 2.0 to 50.0% by mass in total of a water-suspendable polymer other than the polyurethane resin and a water-soluble polymer other than the polyurethane resin.

[0018] <9> The laminate according to any one of <6> to <8>, wherein the ratio of the mass of the polyurethane resin in the barrier layer to the total mass of the water-suspended polymer other than the polyurethane resin and the water-soluble polymer other than the polyurethane resin (mass of the polyurethane resin: total mass of the water-suspended polymer and the water-soluble polymer) is 50:50 to 95:5.

[0019] <10> The laminate according to any one of <1> to <9>, further comprising a primer layer between the paper base layer and the barrier layer.

[0020] <11> The laminate according to any one of <1> to <10>, wherein the sealing layer contains a water-dispersible resin.

[0021] <12> A processed paper product using the laminate according to any one of <1> to <11>. DETAILED DESCRIPTION

[0022] In this specification, "X to Y" indicating a range means "above X and below Y". When a numerical range is described in stages, the upper limit and lower limit of each numerical range may be arbitrarily combined. In addition, in this specification, (meth)acrylic acid refers to a general term for acrylic acid and methacrylic acid. In addition, in this specification, unless otherwise specified, operations and measurements of physical properties are carried out under the conditions of room temperature (20 to 25°C) / relative humidity 40 to 50% RH.

[0023] One embodiment of the present disclosure is a laminate including a thermoplastic resin layer, a paper base layer, a barrier layer, and a sealant layer in this order, wherein the barrier layer contains a polyurethane resin, a swelling layer silicate, and a cationic resin.

[0024] According to the present embodiment, it is possible to provide a laminate that achieves both high gas barrier properties and water vapor barrier properties and further improves the paper ratio (biomass ratio).

[0025] In addition, in this specification, "gas barrier property" means "oxygen barrier property" unless otherwise specified.

[0026] <Thermoplastic resin layer>

[0027] The thermoplastic resin layer is a layer that becomes the outer surface (printing surface) of the paper processed product (e.g., liquid paper container) when the paper processed product is formed, and the thermoplastic resin layer and the sealing layer are heat-sealed when the paper processed product is formed. The thermoplastic resin layer is a layer with thermoplastic resin as the main component, and may also contain components other than thermoplastic resin. In this specification, "main component" means a content of 50% by mass or more, preferably 80% by mass or more, 90% by mass or more (upper limit 100% by mass).

[0028] The resin used for the thermoplastic resin layer is not particularly limited as long as it can be heat-sealed with the sealing layer, and the resin itself is preferably heat-sealed. Specific examples include: low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), ethylene-propylene copolymer, ethylene-butene copolymer, propylene-butene copolymer, propylene homopolymer, propylene-ethylene random copolymer, propylene-ethylene block copolymer, propylene-ethylene-butene copolymer, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-methyl methacrylate copolymer, cyclohexanedimethanol-modified polyethylene terephthalate, Polyester resins such as ethylene glycol copolymers, polymethylpentene, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyester copolymers, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene (ABS) resin, acrylic resin, modified polyphenylene ether (PPE), polyamide resin; biodegradable resins such as polylactic acid (PLA), polyhydroxybutyrate (PHB), polybutylene succinate (PBS), poly(butylene adipate-co-butylene terephthalate) (PBAT), polycaprolactone (PCL), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH), etc. These may be used alone or in combination of two or more.

[0029] The method for forming the thermoplastic resin layer is not particularly limited, and the resin layer can be formed by laminating the resin using a known method, or by applying a coating liquid obtained by dissolving or dispersing the resin in a solvent. In the case of forming the thermoplastic resin layer by lamination, the resin used for the thermoplastic resin layer preferably includes at least one selected from the group consisting of polyethylene and biodegradable resins, more preferably includes at least one selected from the group consisting of low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE) and biodegradable resins, further preferably includes at least one selected from the group consisting of low-density polyethylene (LDPE) and linear low-density polyethylene (LLDPE), and further preferably includes low-density polyethylene (LDPE). Polyethylene is low in cost and has moderate softness, so it is preferably used as a liquid paper container material. In the case of forming the thermoplastic resin layer by coating, acrylic resin is preferably used as the resin for the thermoplastic resin layer. Acrylic resins (especially acrylic copolymers) have the advantages of easy control of physical properties such as heat sealability, printability, and film-forming properties.

[0030] As the acrylic resin, any of commercially available products and synthetic products may be used. Examples of commercially available products include BRITONE FC-640V manufactured by Sakata Inx Co., Ltd., JONCRYL PDX7326 and JONCRYL JDX-6500 manufactured by BASF Japan Co., Ltd., and SEIKOAT RE-2016 and SEIKOAT RE-2194 manufactured by Seiko PMC Co., Ltd.

[0031] The weight per unit area of ​​the thermoplastic resin layer is not particularly limited, but is preferably 1 to 50 g / m 2 , more preferably 2 to 30 g / m 2 The thickness of the thermoplastic resin layer is not particularly limited, but is preferably 5 to 100 μm, more preferably 10 to 50 μm, from the viewpoint of molding processability.

[0032] The thermoplastic resin layer may be formed as a single layer of a single resin, may be formed as a single layer by mixing a plurality of resins, or may be formed as a plurality of layers composed of the same type or different types of resins.

[0033] <Paper base layer>

[0034] The paper substrate used for the paper substrate layer is not particularly limited, and a known paper material can be used.

[0035] The pulp constituting the paper substrate preferably has plant-derived pulp as the main component, and wood pulp as the main component. Examples of wood pulp include hardwood pulp and coniferous wood pulp. Examples of non-wood pulp include cotton pulp, hemp pulp, kenaf pulp, and bamboo pulp. Unless the effects of the present disclosure are impaired, materials other than pulp fibers such as synthetic fibers such as rayon fibers and nylon fibers may be used as the secondary paper material.

[0036] Specific examples of paper substrates include bleached kraft paper, unbleached kraft paper, fine paper, cardboard, liner paper, coated paper, glossy white kraft paper, glassine, and graphan paper. Among them, bleached kraft paper, unbleached kraft paper, fine paper, and glossy white kraft paper are preferred. Bleached kraft paper and glossy white paper are more preferred, and glossy white kraft paper is even more preferred.

[0037] The paper substrate may also contain additives. Examples of additives include pH adjusters (sodium bicarbonate, sodium hydroxide, etc.), dry strength agents (polyacrylamide, starch, etc.), wet strength agents (polyamide polyamine epichlorohydrin resin, melamine-formaldehyde resin, urea-formaldehyde resin), internal sizing agents (rosin, alkyl ketene dimer, etc.), retention and drainage aids, defoamers, fillers (calcium carbonate, talc, etc.), dyes, etc. These additives may be used alone or in combination of two or more. The content of the additives is not particularly limited and may be within the range commonly used.

[0038] (Weight per unit area)

[0039] The weight per unit area of ​​the paper substrate is not particularly limited, but is usually 20 g / m 2 Above and 600g / m 2 For example, if it is used for packaging bags, it is preferably 20g / m 2 Above and 150g / m 2 Below, more preferably 30g / m 2 Above and 100g / m 2 Below, more preferably 40g / m 2 Above and 70g / m 2 In addition, if it is used for liquid paper containers, paper containers, paper cups, etc., it is preferably 150g / m 2 Above and 600g / m 2 Below, more preferably 200g / m 2 Above and 400g / m 2 The following is the basis weight of the paper substrate, which is measured in accordance with JIS P 8124:2011.

[0040] (Paper thickness)

[0041] The thickness of the paper substrate is not particularly limited, but is generally 20 μm or more and 1000 μm or less. For example, if it is used for packaging bags, it is preferably 20 μm or more and 250 μm or less, more preferably 25 μm or more and 170 μm or less, and further preferably 30 μm or more and 100 μm or less. In addition, if it is used for liquid paper containers, paper containers, paper cups, etc., it is preferably 150 μm or more and 1000 μm or less, and more preferably 200 μm or more and 650 μm or less. The thickness of the paper substrate is measured in accordance with JIS P 8118:2014.

[0042] (Wang Yan type smoothness)

[0043] The smoothness of the paper substrate is not particularly limited. For example, the surface on which the barrier layer is provided preferably has a Wohnen smoothness of 5 seconds or more, more preferably 10 seconds or more. The upper limit is not particularly limited, but is preferably 2000 seconds or less, more preferably 1000 seconds or less. It should be noted that the Wohnen smoothness of the paper substrate is measured in accordance with JIS P 8155:2010.

[0044] (Method for producing paper substrate)

[0045] As a method for manufacturing a paper substrate, there can be cited a method of making paper from a paper stock containing pulp. It should be noted that the paper stock may further contain additives. As additives, for example, the additives listed above can be cited.

[0046] The paper stock can be prepared by adding an additive to a pulp slurry. The pulp slurry is obtained by beating pulp in the presence of water. The pulp beating method and the beating device are not particularly limited, and can be the same as the known beating method and beating device. The content of the pulp in the paper stock is not particularly limited, and can be within the range commonly used. For example, it is 60% by mass or more and less than 100% by mass relative to the total mass of the paper stock.

[0047] Papermaking of paper stock can be carried out by conventional methods. For example, the following methods can be cited: the paper stock is cast on a wire or the like, dehydrated to obtain wet paper, multiple wet paper sheets are overlapped as needed, and the single-layer or multi-layer wet paper sheets are pressed to dry. In this case, a single-layer paper is obtained when multiple wet paper sheets are not overlapped, and a multi-layer paper is obtained when multiple wet paper sheets are overlapped. When multiple wet paper sheets are overlapped, an adhesive may be applied to the surface of the wet paper (the surface on which other wet paper sheets are overlapped).

[0048] <Barrier layer>

[0049] The barrier layer comprises a polyurethane resin, a swelling layered silicate and a cationic resin. With such a barrier layer, a laminate having both high gas barrier properties and water vapor barrier properties can be obtained, and the paper ratio (biomass ratio) can be further improved. The barrier layer can be one layer or two or more layers, and is preferably one layer (single layer) from the perspective of manufacturing cost.

[0050] (Polyurethane resin)

[0051] The barrier layer contains a polyurethane resin. The polyurethane resin is not particularly limited as long as it is a polymer having a urethane bond, and a known polyurethane resin can be used.

[0052] From the viewpoint of taking both water vapor barrier property and gas barrier property into consideration at a higher level, the polyurethane resin preferably comprises at least one selected from the group consisting of polyurethane having structural units derived from meta-xylylene diisocyanate and hydroxy polyurethane, and more preferably comprises hydroxy polyurethane. Polyurethane resin is usually obtained by the reaction of polyisocyanate with a polyol having two or more hydroxyl groups, and "polyurethane having structural units derived from meta-xylylene diisocyanate" means a polyurethane resin obtained by the above reaction using a part or all of meta-xylylene diisocyanate as a polyisocyanate. In addition, "hydroxy polyurethane" means a polyurethane resin having a hydroxyl group.

[0053] The hydroxy value of the hydroxy polyurethane is preferably 100 to 500 mgKOH / g, more preferably 150 to 400 mgKOH / g, and even more preferably 200 to 350 mgKOH / g. The above hydroxy value improves the cohesive force of the hydroxy polyurethane and makes it easier to exhibit high barrier properties.

[0054] The hydroxy polyurethane may have an acid group. The acid value of the hydroxy polyurethane is preferably 50 to 100 mgKOH / g, more preferably 10 to 70 mgKOH / g, and further preferably 15 to 60 mgKOH / g.

[0055] The acid value and hydroxyl value of hydroxy polyurethane can be measured by a titration method in accordance with JIS K 1557:2007.

[0056] In the case where the polyurethane resin has a structural unit derived from meta-xylylene diisocyanate, the content of the structural unit derived from meta-xylylene diisocyanate is preferably 50 mol% or more relative to the total amount of the structural unit derived from polyisocyanate. Such a polyurethane resin exhibits high cohesive force due to hydrogen bonds and the stacking effect of the xylylene groups, and is therefore considered to have better gas barrier properties. The above content can be used 1 The samples were identified by known analytical methods such as H-NMR.

[0057] The glass transition temperature of the polyurethane resin is preferably 50° C. or higher, more preferably 65° C. or higher, further preferably 90° C. or higher, and further preferably 110° C. or higher. The upper limit is not particularly limited, but is, for example, 200° C. or lower. The glass transition temperature of the polyurethane resin is a value measured in accordance with JIS K 7121:1987.

[0058] The hydroxy polyurethane may be a commercially available hydroxy polyurethane, for example, HPU W-001, HPU W-003, HPU-W013A (all manufactured by Dainichi Seika Industries, Ltd.), etc. In addition, as a polyurethane having a structural unit derived from meta-xylylene diisocyanate, TAKELAC WPB-341 (30) (manufactured by Mitsui Chemicals, Inc.), etc. may be mentioned.

[0059] The content of the polyurethane resin in the barrier layer is preferably 30.0 to 80.0% by mass, more preferably 40.0 to 75.0% by mass, further preferably 50.0 to 70.0% by mass, further preferably 55.0 to 68.0% by mass, and further preferably 60.0 to 66.0% by mass. By being in the above range, it is easier to improve the water vapor barrier property and the gas barrier property. In addition, if it is in the above range, the strength of the barrier layer is good and the heat sealability of the sealing layer is good.

[0060] (Swelling layered silicate)

[0061] In order to improve the water vapor barrier property and the gas barrier property more easily, the barrier layer contains a swelling layer silicate. The swelling layer silicate is in the form of a plate.

[0062] By including a swelling layer silicate in the barrier layer, the flat swelling layer silicate is easily laminated roughly parallel to the plane (surface) of the paper substrate. In this way, the area where the swelling layer silicate does not exist in the plane direction becomes smaller, so it is easy to suppress the permeation of water vapor. In addition, the flat swelling layer silicate is arranged and exists parallel to the plane of the paper substrate in the thickness direction, so the water vapor in the layer bypasses the swelling layer silicate while passing through, and the permeation of water vapor is suppressed by the maze effect. As a result, the barrier layer easily exhibits excellent water vapor barrier properties.

[0063] The average thickness of the swelling layer silicate is preferably 200 nm or less. The average thickness of the swelling layer silicate is preferably 120 nm or less, more preferably 50 nm or less, further preferably 25 nm or less, and particularly preferably 10 nm or less. When the thickness of the swelling layer silicate is small, the number of layers of the swelling layer silicate in the barrier layer is large, so that high water vapor barrier properties can be exerted. The lower limit of the thickness of the swelling layer silicate is not particularly limited, but is preferably 2 nm or more.

[0064] Here, the average thickness of the swellable layered silicate in the state of being included in the barrier layer is determined as follows: An enlarged photograph of the cross section of the barrier layer is taken using an electron microscope.

[0065] At this time, the magnification is set to about 20 to 30 swellable layered silicates included in the screen. The thickness of each swellable layered silicate in the screen is measured. Then, the average value of the obtained thicknesses is calculated as the average thickness of the swellable layered silicate.

[0066] The average length of the swelling layer silicate is preferably 1 μm or more and 100 μm or less. If the average length is 1 μm or more, the swelling layer silicate is easily arranged in parallel with the paper substrate. In addition, if the average length is 100 μm or less, there is a small possibility that a part of the swelling layer silicate protrudes from the barrier layer. The average length of the swelling layer silicate is more preferably 50 μm or less, further preferably 30 μm or less, and particularly preferably 15 μm or less.

[0067] Here, the average length of the swelling layer silicate in the state of being contained in the barrier layer is calculated as follows. An enlarged photograph of the cross section of the barrier layer is taken using an electron microscope. At this time, the magnification is set to include about 20 to 30 swelling layer silicates in the picture. The length (long diameter) of each swelling layer silicate in the picture is measured. Then, the average value of the obtained lengths is calculated as the average length of the swelling layer silicate. It should be noted that the length of the swelling layer silicate is sometimes also recorded as a particle size.

[0068] The aspect ratio of the swelling layered silicate is preferably 50 or more. If the aspect ratio is 50 or more, it is easier to improve the water vapor barrier. The aspect ratio of the swelling layered silicate is preferably 80 or more, more preferably 300 or more, and particularly preferably 500 or more. The larger the aspect ratio, the more the permeation of water vapor is suppressed, and the more the water vapor barrier is improved. In addition, the larger the aspect ratio, the more the amount of swelling layered silicate added can be reduced. The upper limit of the aspect ratio is not particularly limited. From the perspective of the viscosity of the coating liquid, it is preferably about 10,000 or less, more preferably about 5,000 or less, and further preferably about 2,000 or less. That is, as the preferred range of the aspect ratio, the range of 50 or more and 10,000 or less, 80 or more and 5,000 or less, 300 or more and 2,000 or less, and 500 or more and 2,000 or less can be listed. As described above, the aspect ratio refers to a value obtained by dividing the average length of the swellable layered silicate obtained by taking an enlarged photograph of a cross section of the barrier layer using an electron microscope by the average thickness thereof.

[0069] Specific examples of the swelling layered silicate include mica of the mica group and brittle mica group, bentonite, kaolinite (kaolin mineral), pyrophyllite, talc, smectite, vermiculite, chlorite, septechlorite, serpentine, stilpnomelane, montmorillonite, and the like.

[0070] Among them, in particular, from the viewpoint of improving the barrier properties, it is preferred to contain one or more of mica and bentonite, and mica or bentonite is more preferred. Specific examples of mica include: synthetic mica (e.g., swelling mica, non-swelling mica), muscovite, sericite, phlogopite, biotite, fluorphlogopite (artificial mica), red mica, sodium mica, vanadium mica, illite, tin mica, palagonite, brittle mica, etc. In addition, as a specific example of bentonite, montmorillonite can be listed. They can be used alone or in combination of two or more.

[0071] Swellable layered silicate is a layered inorganic compound that swells in water and is easily cleaved by shearing to a nanometer-level thickness. By combining a polyurethane resin and a swellable layered silicate, a thin swellable layered silicate with a high aspect ratio is dispersed in a polyurethane resin film that originally has high gas barrier performance, and a higher gas barrier performance is exerted by the labyrinth effect.

[0072] Examples of the swelling layered silicate include sodium tetrasilicon mica, sodium hectorite, lithium taeniamite, fluorphlogopite, sodium montmorillonite, and the like.

[0073] The swellable layered silicate is preferably a swellable mica such as sodium tetrasilicon mica. Among commercially available swellable layered silicates, examples of swellable mica include NTO-05 (manufactured by Topy Industries) and Somasif ME300B-4T (manufactured by Katakura & Co-op Agri Co., Ltd.).

[0074] The content of the swelling layered silicate in the barrier layer is preferably 5.0 to 30.0 mass %, more preferably 10.0 to 25.0 mass %, and further preferably 13.0 to 24.0 mass %. Within the above range, the water vapor barrier property and the gas barrier property can be more easily improved.

[0075] (Cationic resin)

[0076] The barrier layer contains a cationic resin in addition to a polyurethane resin and a swelling layered silicate. By using the flat inorganic compound and the cationic resin together, the gas barrier property and the water vapor barrier property are greatly improved, and the water vapor barrier property is particularly improved.

[0077] The surface of the swelling layered silicate particles is easily charged as anions, and the end faces of the particles are easily charged as cations, so the surface and the end faces are easily attracted to each other to form a card-house cohesive structure. By adding a cationic resin, the anionic groups on the particle surface can be blocked with cations, and the card-house cohesive structure can be destroyed. Therefore, the three-dimensional cohesion of the swelling layered silicate can be suppressed, and the swelling layered silicate can be arranged parallel to the plane of the paper substrate, which can fully reflect the maze effect. As a result, it can exert very high gas barrier properties and water vapor barrier properties.

[0078] Specific examples of cationic resins include: polyamide compounds, modified polyamide compounds, polyamine compounds, modified polyamine compounds, polyamide amine-epihalohydrin or formaldehyde condensation reaction products, polyamine-epihalohydrin or formaldehyde condensation reaction products, polyamide polyurea-epihalohydrin or formaldehyde condensation reaction products, polyamine polyurea-epihalohydrin or formaldehyde condensation reaction products, polyamide amine polyurea-epihalohydrin or formaldehyde condensation reaction products, polyamide polyurea compounds, polyamine polyurea compounds, polyamide amine polyurea compounds and polyamide amine compounds, polyvinyl pyridine, amino-modified acrylamide compounds, polyvinylamine, polydiallyl dimethyl ammonium chloride, etc.

[0079] Among them, the cationic resin is preferably a modified polyamide compound, and more preferably a modified polyamide resin. As the modified polyamide resin, a commercially available modified polyamide resin can be used, for example, SPI203(50)H manufactured by Taoka Chemical Industry Co., Ltd. can be mentioned.

[0080] The content of the cationic resin in the barrier layer can be appropriately selected according to the type of materials used for the barrier layer, such as the polyurethane resin and the swelling layered silicate. From the viewpoint of further improving the barrier properties (especially the water vapor barrier properties) and / or the heat sealability, the content of the cationic resin in the barrier layer is preferably 1.0 to 20.0% by mass, more preferably 1.0 to 10.0% by mass, further preferably 1.5 to 8.0% by mass, further preferably 1.8 to 5.0% by mass, and particularly preferably 2.0 to 4.5% by mass.

[0081] The surface charge of the cationic resin is preferably 0.1 to 10 meq / g, more preferably 0.1 to 5.0 meq / g, further preferably 0.1 to 4.0 meq / g, further preferably 0.1 to 2.0 meq / g, and particularly preferably 0.2 to 1.0 meq / g.

[0082] When the surface charge of the cationic resin is not less than the above lower limit, the effect of adding the cationic resin can be more fully obtained. On the other hand, when the surface charge is not more than the above upper limit, the aggregation of the swelling layered silicate can be suppressed and the effect of the cationic resin can be more fully exerted.

[0083] It should be noted that the surface charge of the cationic resin is measured by the following method. First, the polymer as a sample is dissolved in water to obtain a solution with a polymer concentration of 1 ppm. For this solution, 0.001N sodium polyvinyl sulfonate is added dropwise using a charge measuring instrument Mutek PCD-04 (manufactured by BTG) to measure the charge amount.

[0084] (Water-suspended polymer, water-soluble polymer)

[0085] The barrier layer may contain other resins in addition to the polyurethane resin to such an extent that the above-mentioned effects are not impaired. As other resins, there are no particular limitations, and examples thereof include polyolefin resins (polyethylene, polypropylene, etc.), vinyl chloride resins, styrene resins, styrene / butadiene copolymers, acrylonitrile / styrene copolymers, acrylonitrile / butadiene copolymers, ABS resins, AAS resins, AES resins, vinylidene chloride resins, polyurethane resins, poly-4-methylpentene-1 resins, polybutene-1 resins, vinylidene fluoride resins, vinyl fluoride resins, fluororesins, polycarbonate resins, acetal resins, polyphenylene ether resins, polyester resins (polyethylene terephthalate, polybutylene terephthalate, etc.), polyphenylene sulfide resins, polyimide resins, polysulfone resins, polyethersulfone resins, aromatic polyester resins, polyarylate resins, olefin / unsaturated carboxylic acid copolymers, styrene / unsaturated carboxylic acid copolymers, acrylic resins, polyvinyl alcohol and modified resins thereof, polyacrylic acid and salts thereof, polysaccharide resins such as cellulose derivatives, starch and derivatives thereof, natural rubber, ceramics and other naturally derived thermosetting resins and their modified products, etc. These may be used alone or in combination of two or more.

[0086] The water-suspendable polymer other than the polyurethane resin preferably includes at least one selected from the group consisting of styrene-butadiene copolymers, styrene / acrylic acid copolymers, olefin-unsaturated carboxylic acid copolymers and polyolefin resins, and more preferably includes olefin-unsaturated carboxylic acid copolymers. The water-suspendable polymer may be used alone or in combination of two or more.

[0087] The water-soluble polymer other than the polyurethane resin preferably includes at least one selected from the group consisting of vinyl alcohol polymers, polyalkylene imines, (meth) acrylic acid polymers, polyethylene glycol, polyacrylamide, polycarboxylic acids, and water-soluble cellulose derivatives, and more preferably includes at least one selected from the group consisting of vinyl alcohol polymers and polyalkylene imines. If the barrier layer contains polyalkylene imine, the effect of improving the adhesion to the sealing layer can also be obtained. The water-soluble polymers may be used alone or in combination of two or more.

[0088] According to the research of the present inventors, the three components of polyurethane resin, flat inorganic compound and cationic resin are good in terms of barrier properties, but the film-forming property of the barrier layer is not fully considered. Therefore, the present inventors found that by using water-suspended polymers and water-soluble polymers in addition to the three components of polyurethane resin, flat inorganic compound and cationic resin, the film-forming property of the barrier layer is improved, and as a result, the water vapor barrier property and gas barrier property are improved. Hereinafter, water-suspended polymers and water-soluble polymers other than polyurethane resin are collectively referred to as film-forming aids.

[0089] In the case of forming a barrier layer by water-based coating, water-soluble polymers have a superior effect of improving film-forming properties compared to water-suspended polymers. Moreover, from the perspective of improving the water resistance of the barrier layer and making the water vapor barrier property better, it is preferred to use a water-suspended polymer in addition to a water-soluble polymer. That is, the barrier layer preferably contains a water-suspended polymer and a water-soluble polymer. At this time, it is preferred to include an olefin-unsaturated carboxylic acid copolymer as a water-suspended polymer, and it is more preferred to include an ethylene-(meth)acrylic acid copolymer as a water-suspended polymer. In addition, it is preferred to include a vinyl alcohol polymer as a water-soluble polymer, and it is more preferred to include polyvinyl alcohol as a water-soluble polymer.

[0090] The mass ratio of the water-suspendable polymer content to the water-soluble polymer content in the barrier layer (water-suspended polymer: water-soluble polymer) is preferably 20:1 to 1:2, more preferably 10:1 to 2:3, further preferably 5:1 to 3:4, and further preferably 4:1 to 4:5.

[0091] When a water-suspendable polymer and a water-soluble polymer are used in combination, for example, a combination of ethylene-acrylic acid copolymer as a water-suspendable polymer and polyvinyl alcohol as a water-soluble polymer is preferred. In this case, for example, other water-suspendable polymers such as polyethyleneimine or / and water-soluble polymers may also be used in combination. That is, the barrier layer preferably contains a water-suspendable polymer and a water-soluble polymer, and in this case, it is preferred that the water-suspendable polymer and the water-soluble polymer are contained in at least the following combination of (A) or (B).

[0092] (A) Water-suspended polymer: ethylene-acrylic acid copolymer; water-soluble polymer: polyvinyl alcohol.

[0093] (B) Water-suspended polymer: ethylene-acrylic acid copolymer; water-soluble polymer: polyvinyl alcohol and polyethyleneimine.

[0094] (Water-suspended polymer)

[0095] 《Styrene / butadiene copolymers》

[0096] Styrene-butadiene copolymers are copolymers obtained by emulsion polymerization of monomers consisting of styrene compounds such as styrene, α-methylstyrene, vinyltoluene, p-tert-butylstyrene, and chlorostyrene and butadiene compounds such as 1,3-butadiene, isoprene (2-methyl-1,3-butadiene), 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene, as well as other compounds copolymerizable with these.

[0097] As the styrene-based compound, styrene is preferred, and as the butadiene-based compound, 1,3-butadiene is preferred.

[0098] As the styrene-butadiene copolymer, a commercially available one may be used. For example, as an acid-modified styrene-butadiene copolymer adhesive, LX407S12 (manufactured by ZEON Corporation of Japan) and the like are exemplified.

[0099] 《Styrene / Acrylic Copolymer》

[0100] Styrene / acrylic acid copolymers are copolymers obtained by emulsion polymerization of monomers such as styrene, α-methylstyrene, vinyltoluene, p-tert-butylstyrene, and chlorostyrene, and acrylic acid compounds such as acrylic acid, methacrylic acid, (meth)acrylic acid esters, (meth)acrylamide propanesulfonic acid, (meth)acrylic acid sulfonyl alkyl ester sodium salt (the number of carbon atoms of the alkyl group is 2 or more and 3 or less), and other compounds copolymerizable with them. As the styrene compound, styrene is preferred, and as the acrylic acid compound, acrylic acid, methacrylic acid, acrylic acid esters, and methacrylic acid esters are preferred, and acrylic acid and acrylic acid esters are more preferred. As the (meth)acrylic acid esters, acrylic acid alkyl esters are preferred, and the number of carbon atoms of the alkyl group is preferably 1 to 6.

[0101] As the styrene / acrylic acid-based copolymer, a commercially available one may be used. For example, as a styrene-acrylic acid copolymer adhesive, JONCRYL HSL-9012 (manufactured by BASF) and the like are exemplified.

[0102] 《Olefin / unsaturated carboxylic acid copolymer》

[0103] The olefin / unsaturated carboxylic acid copolymer is a copolymer obtained by emulsion polymerization of the following monomers, wherein the monomers are composed of an olefin, especially an α-olefin such as propylene or ethylene, and an unsaturated carboxylic acid such as acrylic acid, methacrylic acid, crotonic acid, cinnamic acid, itaconic acid, fumaric acid, maleic acid, butenetricarboxylic acid, an unsaturated polycarboxylic acid alkyl ester having at least one carboxyl group such as monoethyl itaconate, monobutyl fumarate and monobutyl maleate, and other compounds that can copolymerize with them.

[0104] As the olefin, ethylene or α-olefin is preferred, and ethylene is more preferred. In addition, as the unsaturated carboxylic acid monomer, acrylic acid, methacrylic acid, itaconic acid, fumaric acid, etc. are preferred.

[0105] As the olefin / unsaturated carboxylic acid-based copolymer, an ethylene-(meth)acrylic acid copolymer is preferred, and an ethylene-acrylic acid copolymer is more preferred.

[0106] Specific examples of olefin / unsaturated carboxylic acid copolymers include aqueous dispersions of ethylene-acrylic acid copolymer ammonium salts, which are commercially available as ZAIKTHENE (registered trademark) AC (acrylic acid copolymerization ratio 20%, manufactured by Sumitomo Seika Chemicals Co., Ltd.), and are easily available and usable.

[0107] 《Polyolefin resin》

[0108] As the polyolefin resin, a homopolymer or copolymer of a monomer selected from the group consisting of ethylene and α-olefins is preferred, and polyethylene is more preferred. Commercially available polyolefins may also be used. For example, as a polyolefin resin adhesive, HYDRECT HS (manufactured by DIC Corporation) and the like may be cited.

[0109] (Water-soluble polymer)

[0110] 《Vinyl alcohol polymers》

[0111] Examples of the vinyl alcohol polymer include polyvinyl alcohol. The degree of saponification of the polyvinyl alcohol is preferably 85.0 to 99.5 mol%, more preferably 90.0 to 99.0 mol%. Commercially available polyvinyl alcohols may be used. Examples thereof include the EXCEVAL series (manufactured by KURARAY CO., LTD.).

[0112] 《Polyalkyleneimines》

[0113] From the viewpoint of adhesion to the sealing layer, the polyalkylene imine is preferably a polyalkylene imine having an alkylene carbon number of 1 or more and 5 or less, preferably polyethylene imine. The polyethylene imine may be a linear polyethylene imine or a branched polyethylene imine. In addition, the weight average molecular weight is not particularly limited, but is preferably 300 or more and 1,000,000 or less, and more preferably 1,000 or more and 100,000 or less.

[0114] 《(Meth)acrylic acid polymers》

[0115] Examples of (meth)acrylic acid polymers include polyacrylic acid, polymethacrylic acid, and salts thereof. Examples of salts include sodium poly(meth)acrylate and ammonium poly(meth)acrylate. Commercially available (meth)acrylic acid polymers may also be used. For example, aqueous ammonium polyacrylate solutions include Aron A-30 (manufactured by Toagosei Co., Ltd.).

[0116] Polyethylene glycol

[0117] As polyethylene glycol, polyethylene glycol having any polymerization degree and weight average molecular weight can be used, and the weight average molecular weight is preferably in the range of 60000 to 250000, and more preferably in the range of 100000 to 170000. The weight average molecular weight is a value measured by gel permeation chromatography (standard substance: polystyrene).

[0118] Examples of commercially available products of polyethylene glycol include Alkox R-150 and R-400 manufactured by Meisei Chemical Industry Co., Ltd.

[0119] Polyacrylamide

[0120] As the polyacrylamide, a known polyacrylamide can be used. The degree of polymerization and weight average molecular weight of the polyacrylamide are not particularly limited.

[0121] Polycarboxylic acid

[0122] Examples of the polycarboxylic acid include polymaleic acid, acrylic acid-maleic acid copolymer, and polyglucuronic acid.

[0123] Water-soluble cellulose derivatives

[0124] Examples of the water-soluble cellulose derivatives include methyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, hydroxypropyl cellulose, methyl hydroxypropyl cellulose, and methyl hydroxyethyl cellulose.

[0125] The weight average molecular weight of the water-suspendable polymer and the water-soluble polymer is preferably 10,000 or more, more preferably 20,000 or more, and preferably 10 million or less, more preferably 5 million or less. The weight average molecular weight of the water-suspendable polymer is measured using gel permeation chromatography (standard substance: polystyrene). The weight average molecular weight of the water-soluble polymer is measured using gel permeation chromatography (standard substance: polyethylene glycol).

[0126] The total content of the water-suspendable polymer other than the polyurethane resin and the water-soluble polymer other than the polyurethane resin in the barrier layer is preferably 2.0 to 50.0% by mass, more preferably 5.0 to 45.0% by mass, further preferably 10.0 to 35.0% by mass, and further preferably 15.0 to 25.0% by mass. By being within the above range, it is easier to improve the water vapor barrier property and the gas barrier property.

[0127] The content of the water-suspendable polymer other than the polyurethane resin in the barrier layer is preferably 1.0 to 40.0% by mass, more preferably 5.0 to 30.0% by mass, further preferably 8.0 to 20.0% by mass, and further preferably 10.0 to 18.0% by mass. By being within the above range, it is easier to improve the water vapor barrier property and the gas barrier property.

[0128] The content of the water-soluble polymer other than the polyurethane resin in the barrier layer is preferably 1.0 to 20.0% by mass, more preferably 2.0 to 15.0% by mass, further preferably 2.0 to 10.0% by mass, and further preferably 3.0 to 9.0% by mass. By being within the above range, it is easier to improve the water vapor barrier property and the gas barrier property.

[0129] From the viewpoint of achieving both barrier properties (especially gas barrier properties) and film-forming properties, the mass ratio of the polyurethane resin to the film-forming aid in the barrier layer (polyurethane resin: film-forming aid) is preferably 50:50 to 95:5, more preferably 55:45 to 90:10, further preferably 60:40 to 85:15, and further preferably 65:35 to 85:15. It should be noted that the mass ratio of the polyurethane resin to the film-forming aid refers to the ratio of the mass of the polyurethane resin to the total mass of the water-suspendable polymer other than the polyurethane resin and the water-soluble polymer other than the polyurethane resin (mass of the polyurethane resin: total mass of the water-suspendable polymer other than the polyurethane resin and the water-soluble polymer other than the polyurethane resin).

[0130] The barrier layer may contain a dispersant, a surfactant, a defoaming agent, a wetting agent, a dye, a color tone adjuster, a thickener, etc. as needed, to such an extent that the above-mentioned specific barrier properties are not impaired.

[0131] (Barrier layer coating amount)

[0132] The coating amount of the barrier layer is not particularly limited, but is preferably 1 g / m 2 as a solid content after drying from the viewpoint of barrier properties. 2 More preferably 2g / m 2 From the viewpoint of re-dissociation, 15 g / m 2 Below, more preferably 10g / m 2 Below, more preferably 8g / m 2 Below, more preferably 6g / m 2 That is, the preferred range of the coating amount of the barrier layer is as follows: 1 g / m 2 Above and 15g / m 2 Below, 1g / m 2 Above and 10g / m 2 Below, 2g / m 2 Above and 8g / m 2 Below and 2g / m 2 Above and 6g / m 2 The following range.

[0133] The thickness of the barrier layer is preferably 1 to 20 μm, more preferably 2 to 10 μm.

[0134] (Method for forming barrier layer)

[0135] The method for forming the barrier layer is not particularly limited. For example, a barrier layer coating liquid is prepared by dispersing at least one resin selected from the group consisting of water-suspendable polymers and water-soluble polymers other than polyurethane resins, polyurethane resins, swelling layered silicates, and cationic resins in a solvent. Preferably, the obtained barrier layer coating liquid is applied to a paper substrate and dried to form the barrier layer.

[0136] The solvent of the barrier layer coating liquid is not particularly limited, and water or an organic solvent such as ethanol, isopropyl alcohol, methyl ethyl ketone, toluene, etc. can be used. Among them, from the viewpoint of not causing the problem of volatile organic solvents, the dispersion medium of the barrier layer coating liquid is preferably an aqueous medium, and more preferably water. In this specification, an aqueous medium refers to a medium containing 50% by mass or more of water.

[0137] The device for applying the barrier layer coating liquid is not particularly limited, and may be appropriately selected from commonly used coating devices. Examples thereof include: air knife coater, blade coater, gravure coater, rod blade coater, roll coater, reverse roll coater, Meyer rod coater, curtain coater, slot die coater, Champlex coater, metering blade size press coater, short dwell coater, spray coater, gate roll coater, lip coater, and other well-known coating devices.

[0138] <Sealing layer>

[0139] The sealing layer of this method is a layer that becomes the inner surface (liquid contact surface) of the paper processed product (such as a liquid paper container) when the paper processed product is formed, and the thermoplastic resin layer and the sealing layer are heat-sealed when the paper processed product is formed. The sealing layer is a layer that is melted and bonded by heating, ultrasound, etc. There is no particular limitation on the sealing layer as long as it has heat-sealing properties, and a known resin with heat-sealing properties can be used. The sealing layer is a layer with a resin with heat-sealing properties as the main component, and may also contain components other than the resin with heat-sealing properties (such as wax, pigment, etc.).

[0140] The method for forming the sealing layer is not particularly limited. The sealing layer can be formed by laminating a heat-sealable resin using a known method, or by preparing a sealing layer coating liquid prepared by dissolving or dispersing a heat-sealable resin in a solvent, applying the liquid onto the barrier layer, and drying the liquid to form the sealing layer.

[0141] The sealing layer can be formed by lamination. An adhesive layer can be formed on one surface of a resin film having heat sealability, and the adhesive layer and the barrier layer can be bonded together by dry lamination. Alternatively, the sealing layer can be formed by extrusion lamination without using an adhesive, and a heat sealable resin can be applied to the sealing layer. In the case of dry lamination, aging can also be performed. It should be noted that the oxygen barrier property is sometimes reduced by the influence of heat during extrusion in the extrusion lamination method, so the dry lamination method is preferred.

[0142] In the case of forming a sealing layer by lamination, the resin having heat sealability is preferably at least one selected from the group consisting of polyethylene, polyester resin and biodegradable resin, more preferably at least one selected from the group consisting of low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), polyester resin and biodegradable resin, and further preferably at least one selected from the group consisting of low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE) and polyester resin. In addition, the adhesive layer is not particularly limited, and a known adhesive that can be used for lamination can be used. As an adhesive, a commercially available product can be used, for example, DIC DRY LX-500 / KW-75 (urethane adhesive) manufactured by DIC Corporation, PASLIM VM001 / 108CP (gas barrier urethane adhesive), MAXIVE M-100 (gas barrier epoxy adhesive) manufactured by MITSUBISHI GAS CHEMICAL Co., Ltd., etc.

[0143] The resin film with heat sealability may also be a vapor-deposited film. That is, the laminate of the present embodiment may also have a vapor-deposited layer. The vapor-deposited layer may be a vapor-deposited layer of a metal such as aluminum, or a vapor-deposited layer of an inorganic oxide such as silicon dioxide or aluminum oxide. The vapor-deposited layer may be formed by a known method such as a vacuum vapor deposition method or a sputtering method.

[0144] The thickness of the sealing layer when the sealing layer is formed by lamination is not particularly limited, but is preferably 10 μm or more, more preferably 15 μm or more, from the viewpoint of heat sealability, and is preferably 75 μm or less, more preferably 50 μm or less, from the viewpoint of reducing environmental load. That is, the preferred range of the thickness of the sealing layer when the sealing layer is formed by lamination includes: 10 μm or more and 75 μm or less and 15 μm or more and 50 μm or less.

[0145] The weight per unit area is not particularly limited, but is preferably 10 g / m from the viewpoint of heat sealability. 2 More preferably 15g / m 2 From the viewpoint of reducing environmental load, 75 g / m 2 Below, more preferably 50g / m 2 That is, the preferred range of the weight per unit area of ​​the sealing layer is: 10 g / m 2 Above and 75g / m 2 Below and 15g / m 2 Above and 50g / m 2 The following range.

[0146] In the case of preparing a sealing layer coating liquid in which a heat-sealable resin is dissolved or dispersed in a solvent, applying it on a barrier layer and drying it to form a sealing layer, the sealing layer coating liquid is preferably formed by dispersing a water-dispersible resin in an aqueous solvent. Here, "aqueous" means containing 50% or more water by mass. That is, the sealing layer preferably contains a water-dispersible resin. As a water-dispersible resin, the above-mentioned substances as water-suspended polymers other than polyurethane resins can be listed, and preferably: polyolefin resins, styrene / acrylic copolymers, ethylene-(meth)acrylic acid copolymers and other acrylic resins, ethylene-vinyl acetate copolymers, polyester resins, rubber resins, urethane resins, polyamide resins, etc. They can be used alone or in combination of two or more. Among them, it is preferred to contain an acrylic resin, and more preferably a water-based acrylic resin such as a styrene / acrylic copolymer. The advantages of acrylic resins are as described above. As an acrylic resin, any of commercially available products and synthetic products can be used, and as a commercially available product, the substances exemplified in the item of the thermoplastic resin layer can be used.

[0147] In addition to these resins, lubricants such as paraffin wax, carnauba wax, and polyolefin wax; and pigments such as silica and kaolin may be added for the purpose of preventing blocking and improving oil resistance.

[0148] The solvent for dispersing the water-dispersible resin is not particularly limited, and water or an organic solvent such as ethanol, isopropanol, methyl ethyl ketone, toluene, etc. can be used. Among them, from the viewpoint of not causing the problem of volatile organic solvents, the dispersion medium of the sealing layer coating liquid is preferably an aqueous medium, and more preferably water.

[0149] When the sealing layer is formed by coating, the coating amount is not particularly limited, but is preferably 1 g / m 2 as a solid content after drying from the viewpoint of heat sealability. 2 More preferably 2g / m 2 From the viewpoint of re-dissociation, 20 g / m 2 Below, more preferably 15g / m 2 When the sealing layer is formed by coating, the preferred range of the coating amount is as follows: 1 g / m 2 Above and 20g / m 2 Below and 2g / m 2 Above and 15g / m 2 The following range.

[0150] (Base coating)

[0151] The laminate of this embodiment may have a primer layer (hereinafter also referred to as a clay coating layer) between the paper substrate and the barrier layer. This can plug the pores of the paper substrate and make it smooth, thereby improving the barrier properties.

[0152] The primer layer is preferably formed by applying an aqueous coating liquid formed by inorganic pigments and adhesives being dispersed in an aqueous medium and drying. By forming the primer layer in this way, a primer layer with good plugging effect can be obtained. Moreover, when dissociating again, the components of the primer layer are dispersed in water again, and pulp can be recovered with a high recovery rate (that is, becoming a laminate with excellent recyclability). Therefore, in the laminate, the primer layer is preferably formed by applying an application liquid formed by adhesives being dispersed in an aqueous medium, preferably comprising inorganic pigments and adhesives. In addition, the adhesive is preferably a water-suspended polymer.

[0153] The primer layer preferably comprises an inorganic pigment and a binder, and more preferably is mainly composed of an inorganic pigment and a binder. It should be noted that "the primer layer is mainly composed of an inorganic pigment and a binder" means that the total content of the inorganic pigment and the binder in the primer layer is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, further preferably 80% by mass or more, further preferably 90% by mass or more, and particularly preferably 95% by mass or more (upper limit: 100% by mass or less). It should be noted that the primer layer may also include any component in addition to comprising an inorganic pigment and a binder.

[0154] The inorganic pigment contained in the base coat is not particularly limited, and examples thereof include: clays such as kaolin, talc, and mica, metal oxides, etc., preferably clays, and more preferably kaolin. The inorganic pigment can be used alone or in combination of two or more. The aspect ratio of the inorganic pigment is usually above 1, preferably above 10, more preferably above 20, and further preferably above 30. The upper limit is not particularly limited, but is preferably below 10,000. From the perspective of finely dispersing in the base coat and improving the dissociation of the paper substrate during recovery, it is preferably below 50, and more preferably below 40. That is, as the preferred range of the aspect ratio of the inorganic pigment, examples thereof include: above 1 and below 10,000, above 10 and below 50, above 20 and below 40, and above 30 and below 40. The aspect ratio can be measured by observation using an electron microscope and X-ray diffraction measurement.

[0155] From the viewpoint of finely dispersing in the base coat and improving the dissociation of the paper substrate during recycling, the average particle size of the inorganic pigment is preferably 5 μm or less, more preferably 3 μm or less, and further preferably 1 μm or less. The lower limit is not particularly limited, but is preferably 0.05 μm or more, and more preferably 0.10 μm or more. That is, the preferred range of the average particle size of the inorganic pigment includes: 0.05 μm or more and 5 μm or less, 0.10 μm or more and 3 μm or less, and 0.10 μm or more and 1 μm or less. The average particle size refers to the median particle size (d50) measured by laser diffraction scattering particle size distribution measurement.

[0156] From the viewpoint of recyclability, the content of the inorganic pigment in the primer layer is usually 50% by mass or more, and may be 60% by mass or more, preferably 65% ​​by mass or more. Furthermore, from the viewpoint of improving the adhesion to the paper substrate and further improving the barrier properties, the content of the inorganic pigment in the primer layer is preferably 98% by mass or less, more preferably 95% by mass or less, further preferably 90% by mass or less, and further preferably 85% by mass or less. That is, the preferred range of the content of the inorganic pigment in the primer layer includes: 50% by mass or more and 98% by mass or less, 60% by mass or more and 95% by mass or less, 65% by mass or more and 90% by mass or less, and 65% by mass or more and 85% by mass or less.

[0157] When the binder contained in the primer layer is a water-suspendable polymer, the glass transition temperature of the water-suspendable polymer is preferably 20° C. or lower, more preferably 10° C. or lower, and preferably -5° C. or higher from the viewpoint of recyclability. The glass transition temperature of the water-suspendable polymer is a value measured by the transition temperature measurement method for plastics (JIS K7121: 2012).

[0158] The binder contained in the primer layer is not particularly limited, and examples thereof include: styrene-butadiene resins; (meth)acrylic (co)polymers; styrene-(meth)acrylic resins; olefin-unsaturated carboxylic acid copolymers such as ethylene-acrylic acid copolymers and ethylene-methacrylic acid copolymers; polylactic acid, etc. The binder preferably includes one or more selected from the group consisting of styrene-butadiene resins, styrene-(meth)acrylic resins, olefin-unsaturated carboxylic acid copolymers, and polylactic acid, and more preferably includes one or more selected from the group consisting of styrene-(meth)acrylic resins, ethylene-(meth)acrylic acid copolymers, and polylactic acid.

[0159] (Meth)acrylic acid (co)polymers are (co)polymers of one or more monomers selected from (meth)acrylic acid and (meth)acrylic acid esters. (Meth)acrylic acid esters are not particularly limited, but are preferably alkyl esters of (meth)acrylic acid having 1 to 12 carbon atoms. In addition, styrene-(meth)acrylic acid resins refer to copolymers of styrene and at least one monomer selected from (meth)acrylic acid and (meth)acrylic acid esters.

[0160] The content of the binder in the primer layer is usually 50% by mass or less, and may be 40% by mass or less. From the viewpoint of recyclability, it is preferably 35% by mass or less. From the viewpoint of improving the adhesion to the paper substrate and further improving the barrier properties, it is preferably 2% by mass or more, more preferably 5% by mass or more, further preferably 10% by mass or more, and further preferably 15% by mass or more. That is, the preferred range of the content of the binder in the primer layer includes: 2% by mass or more and 50% by mass or less, 5% by mass or more and 40% by mass or less, 10% by mass or more and 35% by mass or less, and 15% by mass or more and 35% by mass or less.

[0161] Examples of the optional components that may be contained in the primer layer include a dispersant, a surfactant, an antioxidant, an antistatic agent, a dye, a plasticizer, a lubricant, and a release agent.

[0162] From the viewpoint of improving the pore blocking effect, the coating amount (solid content) of the primer layer is preferably 3 g / m 2 More preferably 5g / m 2 From the viewpoint of recyclability, the coating amount (solid content) of the primer layer is preferably 30 g / m 2 Below, more preferably 20g / m 2 That is, the preferred range of the coating amount (solid content) of the primer layer is as follows: 3 g / m 2 Above and 30g / m 2 Below and 5g / m 2 Above and 20g / m 2 The following range.

[0163] The method for forming the undercoat layer is not particularly limited, but is preferably formed by applying a dispersion containing an inorganic pigment and a binder on a paper substrate and drying the dispersion. The dispersion containing the inorganic pigment and the binder is preferably a dispersion using an aqueous medium as a solvent, such as an aqueous dispersion.

[0164] (Other layers)

[0165] The laminate of the present embodiment may also include layers other than the layers described above. For example, it may have an adhesive layer (adhesive resin layer), and in addition, it may have an inorganic material layer when a higher barrier property is required. Known materials can be applied to the adhesive layer and the inorganic material layer. For example, as the inorganic material layer, there can be listed: a vapor-deposited layer vapor-deposited on a resin film, a laminate of a resin film and an aluminum foil, etc. As described above, the vapor-deposited layer can be an aluminum vapor-deposited layer, an aluminum oxide vapor-deposited layer, or a silicon dioxide vapor-deposited layer. The laminate of this embodiment may also have any layer such as a printing layer and a light-shielding layer.

[0166] (Barrier properties of laminated body)

[0167] The water vapor permeability of the barrier laminate of the present embodiment measured under the conditions of 40° C. and 90% RH in accordance with JIS-Z-0208:1976 is preferably less than 50 g / m 2 day, preferably 40g / m 2 ·Day or less, more preferably 30g / m 2 ·Day or less, more preferably 20g / m 2 ·Day or less, more preferably 15g / m 2 ·day or less, more preferably 10g / m 2 ·Day or less, particularly preferably 8g / m 2 The above range indicates that the water vapor barrier property is very high.

[0168] The lower limit is preferably as low as possible, so there is no particular restriction, but it is preferably 0 g / m 2 · More than 1g / m 2 · More than 2g / m 2 · More than 3g / m 2 ·day or more.

[0169] That is, the preferred range of the water vapor permeability of the laminate at 40°C and 90% RH is: 0 g / m 2 ·More than day and less than 50g / m 2 day, 0g / m 2 ·More than 40g / m 2 Less than one day, 1g / m 2 ·More than 30g / m 2 Less than one day, 1g / m 2 · More than 20g / m 2 Less than one day, 2g / m 2 · More than 15g / m 2 Less than one day, 2g / m 2· More than 10g / m 2 Less than one day and 3g / m 2 · More than 8g / m 2 ·Range below day.

[0170] The water vapor permeability can be controlled by, for example, the thickness of the barrier layer or the selection of the components contained in the barrier layer.

[0171] Furthermore, when the laminate is bonded to the CPP film, the oxygen permeability at 23°C and 50% RH is preferably 10.0 mL / m 2 ·day·atm or less. The oxygen permeability is preferably 8.0 mL / m 2 ·day·atm or less, more preferably 5.0mL / m 2 ·day·atm or less, more preferably 3.0mL / m 2 ·day·atm or less, more preferably 2.0mL / m 2 ·day·atm or less, more preferably 1.5mL / m 2 ·day·atm or less, and more preferably 1.0 mL / m 2 ·day·atm or less, particularly preferably 0.5mL / m 2 The above range indicates that the oxygen barrier property is very high.

[0172] The lower limit is preferably as low as possible, so there is no particular restriction, but it is preferably 0.0 mL / m 2 ·day·atm or more, 0.1mL / m 2 ·day·atm or more.

[0173] That is, when the CPP film is bonded to the laminate, the preferred range of the oxygen permeability at 23°C and 50% RH is: 0.0 mL / m 2 ·day·atm or more and 10.0mL / m 2 ·day·atm or less, 0.0mL / m 2 ·day·atm or more and 8.0mL / m 2 ·day·atm or less, 0.0mL / m 2 ·day·atm or more and 5.0mL / m 2 ·day·atm or less, 0.0mL / m 2 ·day·atm or more and 3.0mL / m 2 ·day·atm or less, 0.1mL / m 2 ·day·atm or more and 2.0mL / m 2 ·day·atm or less, 0.1mL / m2 ·day·atm or more and 1.5mL / m 2 ·day·atm or less, 0.1mL / m 2 ·day·atm or more and 1.0mL / m 2 ·day·atm or less and 0.1mL / m 2 ·day·atm or more and 0.5mL / m 2 ·day·Amount below atm.

[0174] The oxygen permeability can be controlled by, for example, the thickness of the barrier layer or the selection of the components contained in the barrier layer.

[0175] Furthermore, when the laminate is bonded to the CPP film, the oxygen permeability at 23°C and 85% RH is preferably 10.0 mL / m 2 ·day·atm or less, more preferably 8.0mL / m 2 ·day·atm or less, more preferably 5.0mL / m 2 ·day·atm or less, more preferably 3.0mL / m 2 ·day·atm or less, and more preferably 2.0mL / m 2 ·day·atm or less, more preferably 1.5mL / m 2 ·day·atm or less, particularly preferably 1.0 mL / m 2 ·day·atm or less.

[0176] The lower limit is preferably as low as possible, so there is no particular restriction, but it is preferably 0.0 mL / m 2 ·day·atm or more, 0.1mL / m 2 ·day·atm or more.

[0177] That is, when the CPP film is bonded to the laminate, the preferred range of the oxygen permeability at 23°C and 85% RH is: 0.0 mL / m 2 ·day·atm or more and 10.0mL / m 2 ·day·atm or less, 0.0mL / m 2 ·day·atm or more and 8.0mL / m 2 ·day·atm or less, 0.0mL / m 2 ·day·atm or more and 5.0mL / m 2 ·day·atm or less, 0.1mL / m 2 ·day·atm or more and 3.0mL / m 2 ·day·atm or less, 0.1mL / m 2·day·atm or more and 2.0mL / m 2 ·day·atm or less, 0.1mL / m 2 ·day·atm or more and 1.5mL / m 2 ·day·atm or less and 0.1mL / m 2 ·day·atm or more and 1.0mL / m 2 ·day·Amount below atm.

[0178] The oxygen permeability at 85% RH satisfying the above range means that sufficient gas barrier properties are exhibited even in a high humidity environment. The oxygen permeability at 85% RH can be set to the above range by selecting a material for the barrier layer.

[0179] (Ratio of paper base material weight)

[0180] The ratio of the weight of the paper substrate is a value obtained by calculating 100% based on the total weight of the laminate as follows.

[0181] (Ratio of the weight of the paper substrate) = (weight of the paper substrate) / (weight of the laminate) × 100

[0182] The weight ratio of the paper substrate is preferably 75% or more, more preferably 80% or more. When the weight ratio of the paper substrate is above the lower limit, a laminate having a high biomass ratio and a reduced environmental load can be provided. The upper limit is not particularly limited, but is usually 99% or less, preferably 95% or less. That is, the preferred range of the weight ratio of the paper substrate includes: 75% or more and 99% or less and 80% or more and 95% or less.

[0183] The laminate of the present embodiment has excellent water vapor barrier properties and gas barrier properties, and therefore can be preferably used as a paper processed product. Examples of paper processed products include: liquid containers, paper containers, paper cups, etc. In addition, the laminate can be preferably used as a paper processed product such as packaging materials for food, cosmetics, daily sundries, medical products, electronic components, etc. The laminate can also be preferably used as a paper processed product such as packaging materials for contents with fragrance / odor. In addition, it can also be preferably used as a paper processed product such as packaging materials for food, cosmetics, daily sundries, medical products, electronic components, etc. that are exposed to high humidity conditions. The laminate can also be a barrier laminate.

[0184] [Liquid container]

[0185] The liquid container can be manufactured by molding the laminate of the present embodiment by a known method. The shape of the liquid container is not particularly limited, and may be, for example, a roof-shaped (gable-topped), rectangular (flat-topped, brick-shaped, straight, etc.), triangular pyramid-shaped, slant-topped, regular tetrahedron-shaped, cup-shaped, tray-shaped, etc. In addition, the liquid container may also have a straw insertion hole, a mouth plug, and a cover member, etc., as long as the barrier properties are not impaired.

[0186] The liquid contained in the liquid container can be any type of food or non-food. There is no particular limitation on the liquid contained in the liquid container, and the following may be listed: alcoholic beverages such as sake, shochu and red wine; dairy beverages such as milk; specialty beverages such as fruit juice, coffee, tea and black tea; ready-to-eat foods, microwavable foods, specialty foods (yogurt, jelly, pudding, etc.), side dishes and other foods accompanied by liquids; pharmaceuticals; chemical products such as car wax, shampoo, conditioner, detergent, shower gel, hair dye, toothpaste, etc.; etc.

[0187] Example

[0188] In order to specifically explain the present disclosure, examples are given below, but the present disclosure is not limited to these examples. It should be noted that, unless otherwise specified, the following operations are performed at 25° C. and a relative humidity of 50% RH. In addition, “parts” and “%” in the examples and comparative examples represent “parts by mass” and “% by mass”, respectively, unless otherwise specified.

[0189] <Example 1>

[0190] To 33.3 parts by mass of an aqueous dispersion of a layered inorganic compound (swellable mica, major diameter (average length) 6.3 μm, aspect ratio 1260, average thickness about 5 nm, solid content concentration 6 mass %, product name: NTS-10NC, manufactured by Topy Industries) were added 5.1 parts by mass of a self-emulsifying emulsion of an ethylene-acrylic acid copolymer (solid content concentration 29.2 mass %, product name: ZAIKTHENE AC, manufactured by Sumitomo Seika Chemicals, Ltd.) while stirring, and further 26.7 parts by mass of a self-emulsifying aqueous emulsion of a hydroxy polyurethane (solid content concentration 30 mass %, product name: HPU-W013A, manufactured by Dainichi Seika Industries, Ltd., hydroxyl value 235 mgKOH / g, acid value 30 mgKOH / g, glass transition temperature 70°C) was added and stirred. 0.57 parts by mass of a modified polyamide resin (surface charge 0.4 meq / g, solid content concentration 53% by mass, product name: SPI203(50)H, manufactured by TAOKA CHEMICAL CO., LTD.) was added thereto and stirred. 5.0 parts by mass of an aqueous solution prepared by dissolving ethylene-modified polyvinyl alcohol (product name: EXCEVAL RS-1717, manufactured by KURARAY CO., LTD.) as a water-soluble polymer in water at a solid content concentration of 10% was further added. Furthermore, 0.30 parts by mass of a 25% by mass ammonia aqueous solution was added and stirred. Furthermore, dilution water was added to make the solid content concentration 19% by mass to prepare a barrier layer coating.

[0191] 5g / m3 in terms of solid content 2 The barrier coating is applied on a surface with a weight of 330 g / m 2 One surface of a paper substrate (OK Pienasu, manufactured by Oji Materia Co., Ltd.) was used.

[0192] The dry weight is 4g / m 2 A solvent-based adhesive (urethane-based, DICDRY LX-500 / KW-75, manufactured by DIC Corporation) was applied to a 40 μm L-LDPE film (FC-S, manufactured by Mitsui Tosei Co., Ltd., metallocene grade) and dried to form an adhesive layer, and then the adhesive layer was laminated to the barrier layer by dry lamination and aged at 40°C for 3 days, thereby laminating a barrier layer, an adhesive layer, and a sealing layer on one side of the paper substrate. Further, the adhesive layer was extruded to form a 20 μm thick (weight per unit area of ​​about 18 g / m 2 ) was applied to the other side of the paper substrate to form a thermoplastic resin layer (LDPE layer), thereby obtaining a laminate.

[0193] <Example 2>

[0194] Without using adhesive, the film was laminated by extrusion lamination with a thickness of 40 μm (weight about 37 g / m 2 ) was applied on the barrier layer to form a sealant layer (LDPE layer). A laminate was obtained in the same manner as in Example 1.

[0195] <Example 3>

[0196] 70 parts by mass of kaolin (Contour Xtreme, manufactured by Imerys, aspect ratio 33, average particle size d50: 0.26 μm) and 30 parts by mass (solid content) of styrene-acrylic resin binder (ACRONAL S504, manufactured by BASF, glass transition temperature 5°C) were mixed to prepare a primer coating liquid. Before applying the barrier coating, the solid content was 6 g / m 2 The primer coating is applied on a surface with a weight of 330 g / m 2 One side of a paper substrate (OK Pienasu, manufactured by OjiMateria Co., Ltd.) was coated with a dry weight of 3 g / m 2 A laminate was obtained in the same manner as in Example 1, except that the barrier layer coating material was applied thereon in the manner of .

[0197] <Example 4>

[0198] Without using adhesive, the film was laminated by extrusion lamination with a thickness of 40 μm (weight about 37 g / m 2 ) was applied on the barrier layer to form a sealant layer (LDPE layer). A laminate was obtained in the same manner as in Example 3.

[0199] <Example 5>

[0200] A laminated body was obtained in the same manner as in Example 4 except that 1 part by mass (solid content) of polyethyleneimine (EPOMIN P-1000, manufactured by Nippon Shokubai) was further added to the barrier layer coating material.

[0201] <Example 6>

[0202] A laminate was obtained in the same manner as in Example 1 except that the L-LDPE film 40 μm was changed to a heat-sealable polyester film 30 μm (DE046, manufactured by Toyobo).

[0203] <Example 7>

[0204] The extrusion lamination method was used to obtain a 20 μm thick (weight about 18 g / m 2) was applied on the sealant layer (L-LDPE layer) of the paper laminate obtained in Example 1 to further form a sealant layer (LDPE layer) to obtain a laminate.

[0205] <Example 8>

[0206] As the thermoplastic resin layer, an aqueous acrylic dispersion (solid content concentration 42% by mass, product name: BRITONE FC-640V, manufactured by SAKATA INX) was diluted with water to a solid content concentration of 22% by mass instead of LDPE by extrusion lamination, with a solid content of 5 g / m 2 A laminated body was obtained in the same manner as in Example 1 except that a layer was formed by coating in a manner of .

[0207] <Example 9>

[0208] As the heat seal layer coating, a coating prepared by diluting an aqueous acrylic dispersion (solid content concentration 42% by mass, product name: BRITONE FC-640V, manufactured by SAKATA INX, styrene-acrylic acid copolymer) with water to a solid content concentration of 22% by mass was used. The solid content was 10 g / m 2 A laminate was obtained in the same manner as in Example 1, except that the coating material was applied on the barrier layer in a manner to form a sealing layer.

[0209] <Example 10>

[0210] As the thermoplastic resin layer, an aqueous acrylic dispersion (solid content concentration 42% by mass, product name: BRITONE FC-640V, manufactured by SAKATA INX, styrene-acrylic acid copolymer) was diluted with water to a solid content concentration of 22% by mass to replace the LDPE by extrusion lamination method, with a solid content of 5 g / m 2 A laminated body was obtained in the same manner as in Example 9 except that a layer was formed by coating in a manner of .

[0211] <Example 11>

[0212] The paper substrate was set to have a unit weight of 220 g / m 2 A laminate was obtained in the same manner as in Example 1 except that the paper substrate was .

[0213] <Example 12>

[0214] A laminated body was obtained in the same manner as in Example 1 except that the amount of modified polyamide-based resin added was changed to 0.19 parts.

[0215] <Example 13>

[0216] A laminated body was obtained in the same manner as in Example 1 except that the amount of modified polyamide-based resin added was changed to 0.95 parts.

[0217] <Example 14>

[0218] As the sealant layer, the L-LDPE film 40 μm was replaced with a heat-sealable silica-alumina dual-deposited polyester film (ECOSYAR SS VE034, manufactured by Toyobo Co., Ltd.) with a dry weight of 4 g / m 2 A solvent-based adhesive (urethane-based, DIC DRY LX-500 / KW-75, manufactured by DIC Corporation) was applied to the surface of the above-mentioned film on the side where the vapor-deposited layer was provided and dried to form an adhesive layer, and then the adhesive layer and the barrier layer were bonded to each other by a dry lamination method. Except for this, a laminate was obtained in the same manner as in Example 1.

[0219] <Example 15>

[0220] A laminate was obtained in the same manner as in Example 14 except that the adhesive was changed to a barrier adhesive (urethane-based, PASLIM VM001 / 108CP, manufactured by DIC Corporation) to form the adhesive layer.

[0221] <Example 16>

[0222] A laminate was obtained in the same manner as in Example 1, except that the amount of the self-emulsifying emulsion of ethylene-acrylic acid copolymer added was changed to 6.8 parts by mass, the amount of the self-emulsifying aqueous emulsion of hydroxy polyurethane added was changed to 23.4 parts by mass, and the amount of the ethylene-modified polyvinyl alcohol aqueous solution (solid content concentration 10% by mass) added was changed to 10.0 parts by mass to prepare a barrier layer coating.

[0223] <Example 17>

[0224] A heat-sealable laminate was obtained in the same manner as in Example 1 except that the self-emulsifying aqueous emulsion of hydroxy polyurethane (solid content concentration 30% by mass, product name: HPU-W013A, manufactured by Dainichi Seika Industries, Ltd.) of the barrier layer coating was changed to a dispersion of polyurethane having a structural unit derived from meta-xylylene diisocyanate (solid content concentration 30% by mass, product name: TAKELAC WPB-341(30), manufactured by Mitsui Chemicals, Inc.). 1As a result of H-NMR measurement, the content of the structural unit derived from meta-xylylene diisocyanate was 50 mol% or more relative to the total amount of the structural unit derived from the polyisocyanate. The polyurethane resin had a glass transition temperature of 130°C.

[0225] <Comparative Example 1>

[0226] A laminate was obtained in the same manner as in Example 1 except that the barrier layer coating material was not applied to the paper substrate.

[0227] <Comparative Example 2>

[0228] The coating amount by the doctor blade method was 6.0 g / m 2 The clay coating coating liquid shown in Table 1 below was applied to the paper substrate and dried, and then the coating amount was 3.0 g / m2 by dry weight by air knife method. 2 A laminated body was obtained in the same manner as in Example 3 except that the barrier layer coating liquid shown in the following Table 2 was applied thereon.

[0229] [Table 1]

[0230] Table 1

[0231]

[0232] [Table 2]

[0233] Table 2

[0234] raw material Amount Engineered kaolin (BARRISURF HX manufactured by Imerys) 100.0 copies Sodium polyacrylate 0.2 parts Polyethyleneimine 3.0 copies Polyvinyl alcohol (PVA117 manufactured by KURARAY Co., Ltd.) 100.0 copies water 1801.8 copies

[0235] <Comparative Example 3>

[0236] A laminate was obtained in the same manner as in Example 1 except that synthetic mica for the barrier layer coating material was not added.

[0237] <Comparative Example 4>

[0238] A laminate was obtained in the same manner as in Example 1 except that the cationic resin of the barrier layer coating material was not added.

[0239] <Comparative Example 5>

[0240] The dry weight is 4g / m 2A solvent-based non-gas barrier adhesive (DIC DRY LX-500 / KW-75, manufactured by DIC Graphics Co., Ltd.) is applied to the alumina vapor-deposited surface of a single-sided alumina vapor-deposited PET film of 12μm (Barrialox 1031HG, manufactured by Toray) to form an adhesive layer. Then, a 60μm L-LDPE film (FC-S, manufactured by Mitsui Tosei Co., Ltd., metallocene grade) is attached to the adhesive layer of the single-sided alumina vapor-deposited PET film as a sealing layer. The adhesive layer is formed by extrusion sandwich lamination with a thickness of 20μm and a unit area weight of 330g / m 2 A paper substrate (OK Pienasu, manufactured by Oji Materia Co., Ltd.) was bonded to one side of the paper substrate using an ethylene-methacrylic acid copolymer (EMAA, NUCREL N0908C, DOW-MITSUIPOLYCHEMICALS Co., Ltd.) as an adhesive, and the obtained laminated film was bonded to one side of the paper substrate in such a way that the adhesive side of the paper substrate was bonded to the single-sided alumina vapor-deposited PET film. The laminated film was further bonded to a thickness of 20 μm (weight of about 18 g / m 2 ) was applied to the other side of the paper substrate to form a resin layer (LDPE layer), thereby obtaining a laminate.

[0241] The following evaluations were performed on the obtained laminated bodies of Examples 1 to 16 and Comparative Examples 1 to 5. The results are shown in Tables 3 and 4.

[0242] [Oxygen permeability]

[0243] The oxygen permeability of the laminate was measured using an oxygen permeability measuring device (MOCON Co., Ltd., OX-TRAN2 / 22) at a temperature of 23°C and a relative humidity of 50% and at a temperature of 23°C and a relative humidity of 85%. Specifically, the oxygen permeabilities of the laminates obtained in the examples and comparative examples at a temperature of 23°C and a relative humidity of 50% and at a temperature of 23°C and a relative humidity of 85% were measured in accordance with JIS K7126-2:2006. The lower the oxygen permeability value, the better the oxygen barrier properties.

[0244] [Water vapor transmission rate]

[0245] The water vapor permeability of the laminate was measured in accordance with JIS-Z-0208:1976 (cup method) B method (40°C ± 0.5°C, relative humidity 90% ± 2%), with the sealant layer on the inner side.

[0246] [Ratio of paper base material weight]

[0247] The ratio of the weight of the paper substrate is calculated as follows based on the total weight of the laminate as 100%.

[0248] (Ratio of the weight of the paper substrate) = (weight of the paper substrate) / (weight of the laminate) × 100

[0249] [Lamination Adhesion]

[0250] Overlap two sets of laminates with the sealing layers facing each other, and use a HEAT SEAL TESTER (manufactured by TESTERSANGYO Co., Ltd., TP-701-B) to heat seal at 180°C, 0.2MPa, and 1 second. Let the heat-sealed test piece stand in a room with a temperature of 23°C±1°C and a humidity of 50%±2% for more than 4 hours. Next, cut the heat-sealed test piece into 15mm wide, use a tensile testing machine, and perform T-peeling at a tensile speed of 300mm / min, and visually evaluate the destructive action. When the paper substrate is destroyed, the adhesion of each layer is high, so it is evaluated as good.

[0251] A: The paper substrate is damaged.

[0252] B: Destruction occurred between the paper and the sealing layer, but the paper base material was not damaged.

[0253] [Table 3]

[0254]

[0255] [Table 4]

[0256]

[0257] [Table 5]

[0258]

Claims

1. A laminate, wherein: The invention comprises a thermoplastic resin layer, a paper substrate layer, a barrier layer and a sealing layer in sequence. The barrier layer comprises a polyurethane resin, a swelling layered silicate and a cationic resin.

2. The laminate according to claim 1, wherein The polyurethane resin includes at least one selected from the group consisting of polyurethane having a structural unit derived from meta-xylylene diisocyanate and hydroxy polyurethane.

3. The laminate according to claim 1 or 2, wherein: The barrier layer contains 1.0 to 20.0 mass % of the cationic resin.

4. The laminate according to any one of claims 1 to 3, wherein The barrier layer contains 30.0 to 80.0 mass % of the polyurethane resin.

5. The laminate according to any one of claims 1 to 4, wherein The barrier layer contains 5.0 to 30.0 mass % of the swelling layered silicate.

6. The laminate according to any one of claims 1 to 5, wherein The barrier layer further comprises at least one selected from the group consisting of a water-suspendable polymer other than a polyurethane resin and a water-soluble polymer other than a polyurethane resin, The water-suspended polymer comprises an olefin-unsaturated carboxylic acid copolymer. The water-soluble polymer includes at least one selected from the group consisting of vinyl alcohol polymers and polyalkylene imines.

7. The laminate according to any one of claims 1 to 6, wherein The barrier layer further comprises a water-suspendable polymer other than the polyurethane resin and a water-soluble polymer other than the polyurethane resin, The barrier layer comprises the water-suspendable polymer and the water-soluble polymer in at least the following combination of A or B, A: Water-suspended polymer: ethylene-acrylic acid copolymer; water-soluble polymer: polyvinyl alcohol, B: Water-suspended polymer: ethylene-acrylic acid copolymer; water-soluble polymer: polyvinyl alcohol and polyethyleneimine.

8. The laminate according to claim 6 or 7, wherein: The barrier layer contains 2.0 to 50.0% by mass in total of a water-suspendable polymer other than the polyurethane resin and a water-soluble polymer other than the polyurethane resin.

9. The laminate according to any one of claims 6 to 8, wherein The ratio of the mass of the polyurethane resin in the barrier layer to the total mass of the water-suspended polymer and the water-soluble polymer other than the polyurethane resin, i.e., the mass of the polyurethane resin: the total mass of the water-suspended polymer and the water-soluble polymer, is 50:50 to 95:

5.

10. The laminate according to any one of claims 1 to 9, wherein A primer layer is provided between the paper substrate layer and the barrier layer.

11. The laminate according to any one of claims 1 to 10, wherein The sealing layer includes a water-dispersible resin.

12. A processed paper product, wherein: The laminate according to any one of claims 1 to 11 is used.

Citation Information

Patent Citations

  • Packaging paper

    JP2021138434A

  • Barrier laminate

    WO2021106891A1